Chiral perspective evaluations: Enantioselective hydrolysis of 6PPD and 6PPD-quinone in water and enantioselective toxicity to Gobiocypris rarus and Oncorhynchus mykiss. (August 2022) - Di, Shanshan; Liu, Zhenzhen; Zhao, Huiyu; Li, Ying; Qi, Peipei; Wang, Zhiwei; Xu, Hao; Jin, Yuanxiang; Wang, Xinquan
Graphical abstract: Highlights: Products 6PPD-Q, 4-DBAP and 4-HDPA were detected in 6PPD water solutions. 6PPD-Q hydrolysis half-lives (12.8–16.3 d) were longer than 6PPD (4.83–64.1 h). For chiral 6PPD and 6PPD-Q, no enantioselective hydrolysis and conversion occurred. 6PPD was highly toxic to G. rarus, and 6PPD-Q was "very highly toxic" to O. mykiss . S -6PPD-Q toxicity was 2.6 times higher than R -6PPD-Q to O. mykiss . Abstract: As a ubiquitous tire antidegradant, N-(1, 3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) is persistently released into the environment. It is highly toxic to aquatic organisms, and its transformation product 6PPD-quinone (6PPD-Q), is "very highly toxic" to Oncorhynchus kisutch at a median lethal concentration (LC50 ) of < 0.1 ng/mL. Notably, 6PPD and 6PPD-Q are chiral compounds. Here, enantioselective evaluations, including hydrolysis and acute toxicity were conducted after preparing the enantiomer, confirming the enantiomer absolute configuration and establishing enantioseparation methods. In the 6PPD hydrolysis experiments, the products 6PPD-Q, phenol, 4-[(1, 3-dimethylbutyl)amino]- (4-DBAP) and 4-hydroxydiphenylamine (4-HDPA) were detected. In different water solutions, the hydrolysis of 4-DBAP and 4-HDPA was very fast (0.87–107 h), while the 6PPD-Q hydrolysis half-lives (12.8–16.3 d) were significantly longer than 6PPD (4.83–64.1 h). At the enantiomeric level, no enantioselective hydrolysis and conversion occurred. R -6PPD generated R -6PPD-Q, and S -6PPD generated S -6PPD-Q, and the formation rate of S -6PPD-Q was 1.77 times faster than R -6PPD-Q. In terms of the enantioselective toxicity, the 6PPD enantiomer was highly toxic to China-specific Gobiocypris rarus (LC50, 162–201 ng/mL), and it had no enantioselective difference. 6PPD-Q was "very highly toxic" (LC50, 1.66–4.31 ng/mL) to Oncorhynchus mykiss, which is of commercial importance, and the toxicities of rac -6PPD-Q and S -6PPD-Q were 1.9 and 2.6 times higher than R -6PPD-Q. Furthermore, the formation concentrations of S -6PPD-Q and R -6PPD-Q in 6PPD water solutions were higher than the LC50 values of O. kisutch and O. mykiss, and the toxicity of 6PPD-Q was highly species-specific, which should raise concern. These results provide important information for environmental risk assessments of 6PPD and 6PPD-Q, especially from the perspective of enantiomers.